INCLUSIVE EDUCATION IN THE REPUBLIC OF UZBEKISTAN: PROBLEMS AND SOLUTIONS - Sulaymanova Muhlisa Kozimjon qizi (Sciental Journals Publishing, 2025)
This article is devoted to the main problems and solutions in the process of introducing and developing inclusive education in the Republic of Uzbekistan. It analyzes the theoretical foundations of inclusive education, the reforms being implemented in Uzbekistan, the legal framework, infrastructural challenges, the teacher training system, and the attitude of society. Based on the best practices of various countries, the paper presents proposals and recommendations for improving inclusive education under Uzbekistan’s conditions.
Keywords: Inclusive education, disability, educational reforms, legal framework, infrastructure, teaching staff, social readiness, Uzbekistan.